2019
DOI: 10.18203/2394-6040.ijcmph20195071
|View full text |Cite
|
Sign up to set email alerts
|

A study on length of stay and its predictors among dengue patients in a tertiary care institute in Lucknow

Abstract: Background: Dengue virus infection is a growing health problem and is prevalent throughout India. Research focusing on length of hospital stay and its predictors is scarce from India. This is important considering the burden of the disease during epidemics and impact on hospital admissions. Hence the study was conducted with the objectives to find out the factors influencing the length of stay in hospital of dengue patients.Methods: A cross sectional retrospective observational study conducted at a tertiary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In the present study the mean duration of hospital admission was 4.07±1.4 days which is comparable to a study done in Lucknow by Mishra et elsewhere it is 5.44±2.77 days. 16 In the present study fever (87.1%) was the common symptom. Body ache was reported in 50.4% of cases unlike in a study by George et al where 71% of the patients had body ache.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study the mean duration of hospital admission was 4.07±1.4 days which is comparable to a study done in Lucknow by Mishra et elsewhere it is 5.44±2.77 days. 16 In the present study fever (87.1%) was the common symptom. Body ache was reported in 50.4% of cases unlike in a study by George et al where 71% of the patients had body ache.…”
Section: Discussionsupporting
confidence: 54%
“…SGOT value of more than 1000 IU/L indicates the severity of the disease along with morbidity and mortality. 7,9 Additionally, the study done by Mishra et al observed an elevation in SGOT levels in 47.4% of the cases studied.…”
Section: Discussionmentioning
confidence: 89%
“…The disease in India is prevalent in most metropolitan cities and towns, with frequent outbreaks of disease, and case fatality rates as high as 3-5%. 7 There is no specific antiviral therapy for dengue with the mainstay of therapy being supportive and symptomatic with intravenous fluids and electrolytes management. Hence, diagnosis and intervention with close monitoring can reduce the mortality to <1%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation